Association of psychiatric comorbidities with the risk of transport accidents in ADHD and MPH. (15th February 2021) - Liu, Yi-Chun; Chen, Vincent Chin-Hung; Yang, Yao-Hsu; Chen, Yi-Lung; Gossop, Michael
Abstract: Aims: Although the relationship between attention-deficit/hyperactivity disorder (ADHD) and transport accidents has been shown, there is limited information on the relationship between medication and dose–response effects and transport accident risk. This study aims to determine whether young people with ADHD, including adolescents, are more prone to transport accidents than those without, and the extent to which methylphenidate (MPH) prescription in these patients reduces the risk. Methods: We identified 114 486 patients diagnosed with ADHD from Taiwan's National Health Insurance Research Database from 1997 to 2013. Using a Cox regression model, we compared the risk of transport accidents between ADHD and non-ADHD groups and estimated the effect of MPH on accidents. Furthermore, we applied a self-control case-series analysis to compare the risk of accidents during the medication periods with the same patients' non-medication periods. Results: Male ADHD patients had a higher risk of transport accidents than non-ADHD individuals (adjusted hazard ratio [aHR] = 1.24, [95% confidence interval (CI) 1.10–1.39]), especially for those comorbid with epilepsy, oppositional defiant disorder/conduct disorder (ODD/CD), and intellectual disabilities (ID). Female ADHD patients showed no relationship, except for comorbid with autism spectrum disorder (ASD) or ID. We found a reduced risk of transport accidents in patients with ADHD with MPH medication than those without MPH, with a plausible dose–response relationship (aHR of 0.23 to 0.07). A similar pattern was found in self-controlled case-series analysis. Conclusions: Male patients with ADHD, especially those comorbid with epilepsy, ODD/CD, or ID, were at high risk of transport accidents. Female patients, when comorbid with ASD or ID, also exhibited a higher risk of accidents. MPH treatment lowered the accident risk with a dose–response relationship.